2018
DOI: 10.1177/0194599818806271
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Analysis of Human Tracheal Tissue during Decellularization

Abstract: Objective To use mid-infrared (IR) spectroscopy to assess changes in the cartilaginous framework of human trachea during decellularization. Study Design Laboratory-based study. Setting Research laboratory. Methods Six cadaveric human tracheas were decellularized using a detergent enzymatic method (DEM). Tissue samples were obtained from each specimen after 0, 1, 10, and 25 DEM cycles for histologic and spectroscopic analysis. Decellularization was confirmed using hematoxylin and eosin (H&E) and 2-(4-amid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
(96 reference statements)
0
5
0
Order By: Relevance
“…However, FTIR can assess the composition of the extracellular matrix [31] and can produce standardised repeatable results. To date, it has been used to assess the ECM finger print in fibrocartilage bio-scaffold for bone-tendon interface [32] and in the evaluation of de-cellularised human tracheal samples [33]. It has not to our knowledge been used to determine the presence of any residual detergent or enzymes remaining in biological tissue following de-cellularisation.…”
Section: Discussionmentioning
confidence: 99%
“…However, FTIR can assess the composition of the extracellular matrix [31] and can produce standardised repeatable results. To date, it has been used to assess the ECM finger print in fibrocartilage bio-scaffold for bone-tendon interface [32] and in the evaluation of de-cellularised human tracheal samples [33]. It has not to our knowledge been used to determine the presence of any residual detergent or enzymes remaining in biological tissue following de-cellularisation.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, as regards tracheal cartilage, Macchiarini et al [28], Gonfiotti et al [37], Baiguera et al [38], and Elliott et al [30] experienced a detergent enzymatic approach by means of 4% sodium deoxycholate, dH 2 O, and 2000 KU (Kunitz Units) DNase-I in 1 M NaCl followed by further washes in dH 2 O. A slight change to this protocol was recently reported; in fact Tint et al [39] worked with tracheas which were previously freezed in liquid nitrogen and rinsed in a solution of 2 mM CaCl 2 and 1.3 mM MgSO 4 after DNase treatment. However, in all the reported experiences, a complete decelluarization of human trachea required several cycles for a period of three to eight weeks.…”
Section: Cartilagementioning
confidence: 99%
“…Among them, 4% sodium deoxycholate (SDC) in combination with DNase is the most commonly used. [4][5][6][7][8][9][10][11][12] Some authors have reported acceptable degrees of decellularization using other detergents such as sodium dodecyl sulfate (SDS), Triton X-100 or 3-((3-cholamidopropyl) dimethylammonio)-1-propanesulfonate (CHAPS) alone or in combination. [13][14][15][16][17][18][19][20] However, in many cases the authors have directly extrapolated the decellularization protocols reported in the literature, without considering important aspects such as differences in the composition of the extracellular matrix that exist between species.…”
Section: Introductionmentioning
confidence: 99%